EXPLORING STUDENTS' THINKING PROCESSES IN MATHEMATICAL PROBLEM SOLVINGBASED ON THE DEWEY MODEL AT MINHAJUT THULLAB QUR'AN SCIENCE JUNIOR HIGH SCHOOL - Chindi Yuliana Sari (FKIP Universitas Muhammadiyah Tangerang, 2026)
ResearchThis research was motivated by the low ability of students in solvingmathematical problems that require reflective thinking. This study aims toexplore the stages and strategies of students' thinking in solvingmathematical problems at SMP Sains Qur'an Minhajut Thullab, East Lampung. The researchused an exploratory descriptive qualitative approach with sixeighth-grade students as subjects selected purposively. Data were collectedthrough tests, interviews, and observations, then analysed using theMiles and Huberman model and validated by triangulation of sources and methods. The resultsof the study show that the students' thinking processes reflect the stages ofproblem solving according to Dewey's model, with variations in the consistency ofits application. Students with high abilities are able to follow almost allstages of reflective thinking systematically, while students with moderate abilitiesonly reach the stages of reasoning and verification of results, and studentswith low abilities tend to stop at the stage of drawing conclusions withoutdeep reflection. This variation shows that the level of reflective thinking ability affects the completeness of the stages of mathematical problem solving,so that strengthening metacognitive aspects and reflective thinking exercises are necessaryto improve the effectiveness of mathematics learning.